2014
DOI: 10.1111/mcn.12150
|View full text |Cite
|
Sign up to set email alerts
|

Disempowered, passive and isolated: how teenage mothers' postnatal inpatient experiences in the UK impact on the initiation and continuation of breastfeeding

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Labour Ward: disempowered and passive'; 'the postnatal ward: alien, alone and exposed'; and 'being there: a need for relational support' were identified. Sub-themes on Labour Ward were 'feelings at birth: 'so tired and so dazed'; 'deliver, stitch, dress' and 'initiating feeding'. Participants described care that followed set routines, discouraging their initiating breastfeeding by compounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…Application of this medical model prompted the healthcare team to control breastfeeding using excessive monitoring and early 'hands on' support to minimise risks of morbidity but ignored evidence that supports infant self-attachment promoting wellbeing in both mother and baby (Bergman, 2013) including self-efficacy in the mother. This medicalised approach where women quietly complied with the 'hands on' practice, in direct contrast to their later expression of surprise regarding lack of consent and dislike of this corporal invasion, has been highlighted elsewhere (Burns et al, 2013;Hunter et al, 2015). In addition, feelings of humiliation, intimidation and insecurity were triggered when mothers felt forced to expose their breasts for someone to watch feeding, as reported by teenage mothers (Hunter et al, 2015) and mothers with severe breastfeeding difficulties (Palmér et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Application of this medical model prompted the healthcare team to control breastfeeding using excessive monitoring and early 'hands on' support to minimise risks of morbidity but ignored evidence that supports infant self-attachment promoting wellbeing in both mother and baby (Bergman, 2013) including self-efficacy in the mother. This medicalised approach where women quietly complied with the 'hands on' practice, in direct contrast to their later expression of surprise regarding lack of consent and dislike of this corporal invasion, has been highlighted elsewhere (Burns et al, 2013;Hunter et al, 2015). In addition, feelings of humiliation, intimidation and insecurity were triggered when mothers felt forced to expose their breasts for someone to watch feeding, as reported by teenage mothers (Hunter et al, 2015) and mothers with severe breastfeeding difficulties (Palmér et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study the authors found patient, encouraging positive support from health professionals who built confidence were amongst strategies that helped women to be able to breastfeed (Ryan et al 2017). Skilled support from health professionals is important but previous research has indicated that this may not be effective in helping women learn (Guyer et al 2012;Hunter et al 2015;McInnes and Chambers 2008;Redshaw and Henderson 2012). Given the sharp drop in breastfeeding in the first few days after birth it is crucial we improve our understanding of this time.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent mothers often lack breastfeeding knowledge and skills, lack of breastfeeding support from families and health providers, and perceive breastfeeding difficulties such as latching techniques, positioning, management of breastfeeding problems, and fatigue (Monteiro et al, ; Nesbitt et al, ; Tucker, Wilson, & Samandari, ) as general breastfeeding concerns (Balogun, Dagvadorj, Anigo, Ota, & Sasaki, ). At the same time, the evidence reports a number of unique troubles concerning breastfeeding decisions such as infant dependency, physical image, and social criticism/judgement (Hunter & Magill‐Cuerden, ; Hunter, Magill‐Cuerden, & McCourt, ). Unfortunately, there is limited published data on exclusive breastfeeding determinants in adolescent mothers.…”
Section: Introductionmentioning
confidence: 99%